Unraveling the causal role of immune cells in gastrointestinal tract cancers: insights from a Mendelian randomization study - Wang, Yu-xiang; Zhou, Chao-ping; Wang, Da-tian; Ma, Jun; Sun, Xue-hu; Wang, Yao; Zhang, Ya-ming (Frontiers in Immunology, 2024)
Despite early attempts, the relationship between immune characteristics and gastrointestinal tract cancers remains incompletely elucidated. Hence, rigorous and further investigations in this domain hold significant clinical relevance for the development of novel potential immunotherapeutic targets.We conducted a two-sample Mendelian randomization (MR) analysis using the tools available in the "TwoSampleMR" R package. The GWAS data for these 731 immune traits were sourced from the GWAS Catalog database. Concurrently, data on gastrointestinal tract cancers, encompassing malignant tumors in the esophagus, stomach, small intestine, colon, and rectum, were extracted from the FinnGen database. The immune traits subjected to MR analysis predominantly fall into four categories: median fluorescence intensities (MFI), relative cell (RC), absolute cell (AC), and morphological parameters (MP). To ensure the reliability of our findings, sensitivity analyses were implemented to address robustness, account for heterogeneity, and alleviate the impact of horizontal pleiotropy.A total of 78 immune traits causally linked to gastrointestinal tract cancers were identified, encompassing esophageal cancer (12 traits), gastric cancer (13 traits), small intestine cancer (22 traits), colon cancer (12 traits), and rectal cancer (19 traits).Additionally, 60 immune traits were recognized as protective factors associated with gastrointestinal tract cancers, distributed across esophageal cancer (14 traits), gastric cancer (16 traits), small intestine cancer (7 traits), colon cancer (14 traits), and rectal cancer (9 traits). Furthermore, it was observed that seven immune traits are causally related to gastrointestinal tract cancers in at least two locations. These traits include "CCR2 on CD14-CD16+ monocyte," "CD19 on IgD+ CD38-," "CD19 on IgD+ CD38-naive," "CD25hi CD45RA+ CD4 not Treg AC," "CD27 on unsw mem," "CD28 on CD39+ activated Treg," and "CD45 on CD4+."This study elucidates a causal link between immune cells and gastrointestinal tract cancers at various sites through genetic investigation. The findings of this research open up new perspectives and resources for exploring tumor prevention strategies and immunotherapeutic targets.